WOMEN MANAGING FOREST: CASE IN GUNUNGKIDUL AND KULON PROGO REGENCIES, YOGYAKARTA SPECAL PROVINCE, INDONESIA - Fajarwati, Alia; S. Hadiwijoyo, Suryo; W Safina, Shafa; L Helena, Hillary (KRITIS, 2025)
ABSTRACT The relationship between women and forests is manifested through women's involvement in maintaining forest ecosystems. The involvement of women in forest management is one of the strategic issues in the Special Region of Yogyakarta Province. This study aims to analyze forest management activities and assess the impact of forest management activities on women. This study used a qualitative descriptive analysis with the framework of Harvard model gender analysis. This study took place in the Special Region of Yogyakarta, and used 2 locations as case studies, namely Beji Village (Gunungkidul Regency) and Hargowilis Village (Kulon Progo Regency). In Gunungkidul Regency, forest management is directed towards conservation activities, while in Kulonprogo Regency it is forest utilization for agricultural activities. The impacts felt by the women (and men) of the Ngudi Lestari Ranger Group are more on ecological and social benefits. Meanwhile, the Mengger Rejo Forest Farmer Group also receives economic benefits that are equally felt by both genders. This study shows that forests in different locations with different geographic and socio-demographic characteristics will result in different management systems. However, both locations of this study show that women have an important role in forest management.